Syrians in Beirut post-2011 - Shmaitilly, Sarah (2020)
With more than a million Syrians arriving to Lebanon since 2011, most studies have been focusing on refugees in encampment or on the precarious lives working-class Syrians lead. This thesis aims to fill a gap in the literature which overlooks a group of Syrians who now are part and parcel of the social and cultural life in Beirut; the middle and upper-class. Drawing primarily on the theoretical concepts of Pierre Bourdieu and data collected from semi-structured, in-depth interviews, the thesis explores these non-refugees’ economic, social, and cultural capitals and how they were utilized to settle and informally integrate in the city. It illustrates how the working-class Syrians are at the receiving end of discrimination by the Lebanese state and people, while the rich enjoy various privileges like access to citizenship, higher education, well-paying jobs, more respect, and an overall better experience of settlement in a new setting.